THE EFFECT OF TAPPING THERAPY ON BLOOD GLUCOSE LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS AT PURWOKERTO - Atyanti Isworo; Wahyu Ekowati (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2014)
Introduction: Diabetes Mellitus (DM) is a chronic metabolic disease that can lead to microvascular and macrovascular complications. This condition makes DM patients at higher risk of experiencing stress. Tapping Therapy is one of nursing intervention that can reduce stress. The purpose of this study was to identify the effect of tapping therapy on blood glucose levels in Primary Health Center South Purwokerto. Methods: This research was a quantitative with a quasi experimental with control group, recruited 30 respondents, consisted of 15 respondents who were trained on tapping therapy, one time daily for 30 minutes for four weeks and the other respondents were as the control group. The purposive sampling was used as the sample collection method. Wilcoxon test was employed to examine the differences of the mean of blood glucose levels between intervention and control groups. Results. The result revealed that there was a significant difference of blood glucose levels before and after treatment in intervention group (p = 0.003, α =0.05). Discussion: The conclusion was that the tapping therapy can decrease blood glucose level on type 2 diabetes mellitus patients at Purwokerto. This research recommendation was to apply tapping therapy to patient with diabetes mellitus at least one time daily for 30 minute. Keyword: blood glucose, diabetes, tapping therapy